Analysis and application of pan-video playback quality evaluation model - Hua DING; Xin WANG; Zheng WEI; Chuanfei LUO; Hao SONG; Weijia SHI (Dianxin kexue)
Pan-video refers to the business that takes video as the form of information presentation and interaction.It is mainly divided into three categories: traditional video business, emerging video business and derivative video business.However, how to accurately evaluate the quality of video playback has always been a problem.A pan-video playback quality evaluation model and parameters were proposed, which mainly included: video switching delay, video start delay, video playback pause times and duration, etc.It has been applied in the IPTV quality monitoring system of the current network, and the practice shows that the application effect is good.The proposed research results can be further applied to all pan-video application scenarios in the field of video network products.